Thermal and non‐thermal processing technologies on intrinsic and extrinsic quality factors of tomato products: A review - Jayathunge, K.G.L.R.; Stratakos, Alexandros Ch.; Pando, Gonzalo Delgado‐; Koidis, Anastasios (J Food Process Preserv., 2019)
Tomato and tomato‐based products play a vital role in human diet due to the pres‐ ence of bioactive compounds. The conventional heat treatment is designed as a cur‐ rent practice in tomato products industry to ensure food safety but it can lead to undesirable changes both in the nutritional and in the sensory properties of the prod‐ ucts. In order to avoid these unfavorable changes during the heat treatment, novel thermal, and non‐thermal processing technologies have been receiving much atten‐ tion with the aim of improving and replacing conventionally processed products. Among them, some of the most promising technologies of high pressure processing, pulsed electric fields, and power ultrasound in comparison to conventional thermal processing technologies are highlighted in this article. This review presents recent scientific information on impact of these technologies on physico‐chemical, organo‐ leptic, and microbial properties of tomato‐based products. Furthermore, it analyses and discusses the opportunities and drawbacks in commercial applications. Practical applications The preservation of tomato and tomato products is of primary interest for the food industry. Several novel thermal and non‐thermal technologies—discussed in this re‐ view—could be utilized for the production of high quality tomato‐based products. These technologies are increasingly attracting the attention of food processors as they efficiently provide products with extended shelf life and higher quantities of labile bioactive compounds when compared to conventionally processed products